Integrating wildfire resistance and environmental concerns into a sustainable forest ecosystem management approach - Ferreira, Liliana; Nascimento Baptista, Alexandra; Constantino, Miguel; Marques, Susete; Martins, Isabel; Borges, Jose G. (Frontiers in Forests and Global Change, 2023)
This research aims at presenting landscape management planning methods to help stakeholders select forest ecosystem management plans that may address concerns with wildfire risk and with the environmental impacts of clearcuts. Specifically, we develop mixed integer programming models for spatial optimization that incorporate a wildfire resistance index as well as constraints on the size of clearcut openings. The former is used to enforce a minimum level of resistance to wildfire while the latter limits the size of openings, in each period of the planning horizon. Timber volume even flow is another concern that is also taken into account. This research is applied to the Zonas de Intervenção Florestal (ZIF) de Paiva and de Entre-Douro e Sousa (ZIF_VS) which are located in northwestern Portugal.